Behind closed doors - Paris, B. A. (New York : St. Martin's Press, 2016)
The perfect marriage? Or the perfect lie? Everyone knows a couple like Jack and Grace. He has looks and wealth, she has charm and elegance. You might not want to like them, but you do. You'd like to get to know Grace better. But it's difficult, because you realise Jack and Grace are never apart. Some might call this true love. Others might ask why Grace never answers the phone. Or how she can never meet for coffee, even though she doesn't work. How she can cook such elaborate meals but remain so slim. And why there are bars on one of the bedroom windows.
Keywords: Married people -- Fiction; Abused women -- Fiction; Psychopaths -- Fiction; Abusive men -- Fiction; Wife abuse -- Fiction; Sisters -- Fiction; Family secrets -- Fiction; Psychological thrillers; Domestic fiction